2020
DOI: 10.1111/jdv.16265
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of TNF blockers and of ustekinumab in palmoplantar pustulosis and in acrodermatitis continua of Hallopeau

Abstract: Background Palmoplantar pustulosis (PPP) and acrodermatitis continua of Hallopeau (ACH) are rare variants of psoriasis. Knowledge of the efficacy of biologics is scarce. Objectives To evaluate the real-life efficacy of tumour necrosis factor blockers and ustekinumab in PPP and in ACH. Methods A multicentre retrospective descriptive study was conducted in 19 dermatology departments, including all patients with PPP or ACH seen from 2014 to 2016 who received one of the studied biologics. The data were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…La PPP es una afección de difícil tratamiento, ya que la respuesta a los tratamientos sistémicos típicos como fotoquimioterapia, ciclosporina, retinoides y metotrexato es en general escasa 1 . Durante los últimos años, el uso de fármacos biológicos ha surgido como una alternativa [3][4][5][6] . El ustekinumab es un anticuerpo monoclonal humano que se une con alta especificidad y afinidad a la subunidad p-40 de las interleucinas 12 y 23 y bloquea la diferenciación de los linfocitos T colaboradores hacia Th1 y Th17, lo que reduce la liberación de IL-17 y por lo tanto la activación y migración de los neutrófilos 2,4-6 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La PPP es una afección de difícil tratamiento, ya que la respuesta a los tratamientos sistémicos típicos como fotoquimioterapia, ciclosporina, retinoides y metotrexato es en general escasa 1 . Durante los últimos años, el uso de fármacos biológicos ha surgido como una alternativa [3][4][5][6] . El ustekinumab es un anticuerpo monoclonal humano que se une con alta especificidad y afinidad a la subunidad p-40 de las interleucinas 12 y 23 y bloquea la diferenciación de los linfocitos T colaboradores hacia Th1 y Th17, lo que reduce la liberación de IL-17 y por lo tanto la activación y migración de los neutrófilos 2,4-6 .…”
Section: Discussionunclassified
“…Está indicado para psoriasis de moderada a grave y existen algunos casos descritos de pacientes con PPP tratados con ustekinumab que han obtenido respuestas favorables sin efectos adversos significativos, al utilizar dosis que varían entre 45 y 90 mg subcutáneos, administrados entre ocho y 12 semanas. En la actualidad, otras alternativas terapéuticas incluyen guselkumab, etanercept, secukinumab, brodalumab, ixekizumab y apremilast [3][4][5][6] . Están en curso estudios clínicos con inhibidores de la IL-1 (anakinra), inhibidores del receptor tipo B de la IL-8 (RIST4721/AZD4721), inhibidor del receptor A de la IL-17 (brodalumab), inhibidores de la IL-36 (ANB019 y BI655,130) y un inhibidor del receptor del factor estimulador de colonias de granulocitos (CSL324), entre otros 1 .…”
Section: Discussionunclassified
“…Several case reports revealed that ustekinumab can be used to treat ACH patients who failed to respond to anti-TNF agents [58][59][60][61][62]. Another study found no difference in clinical response to ustekinumab and anti-TNF agents in PPP or ACH patients [63]. (Table 2).…”
Section: Anti-il-12/23mentioning
confidence: 99%
“…Case reports suggest that adalimumab is a therapeutic option for severe therapy-resistant ACH [58,90,[129][130][131][132][133]. Of [63]. (Table 4)…”
Section: Anti-tnfαmentioning
confidence: 99%
“…Case reports describing the use of several therapies, including biologics, have been published, and IL‐17 inhibitors seem to be highly effective 1,4 . Despite partial successes with the biologics used so far, a recent French multicentric study – directly comparing several TNF‐α inhibitors and ustekinumab – has shown therapeutic response in a significantly lower manner than for plaque psoriasis, emphasizing the complexity and the need for a constant search for new therapeutic alternatives 5 …”
Section: Figurementioning
confidence: 99%